THE INTEGRATION OF SPIRITUALITY AND SOCIAL TRANSFORMATION IN PESANTREN LEADERSHIP: AN ANALYSIS OF NYAI HJ. MASRIYAH AMVA’S LEADERSHIP MODEL - Alwiyah, Lulu; Farihin; Yani, Ahmad (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2025)
This study explores the leadership model of Nyai Hj. Masriyah Amva, a female Islamic scholar and leader of the Kebon Jambu al-Islamy Islamic Boarding School in Cirebon, Indonesia. Positioned within the historically patriarchal structure of pesantren leadership, her role represents a transformative shift. The research aims to analyze the Islamic spirituality that underpins her leadership, identify the social transformations resulting from her leadership style, and formulate a model of transformational leadership based on the integration of spirituality and social change. Using a qualitative approach and intrinsic case study method, data were collected through in-depth interviews, participatory observation, and document analysis. The findings show that Nyai Masriyah's leadership is grounded in ethical and prophetic spirituality, which functions both vertically (relation to God) and horizontally (social ethics). Her leadership has initiated significant structural and cultural changes in the pesantren environment, such as the inclusion of women in decision-making, gender-sensitive curriculum development, and broader engagement with social issues. The study proposes a conceptual model of Islamic Transformational Leadership rooted in spiritual values, social justice, and gender equality. It offers a contextual and replicable framework that contributes both theoretically to Islamic leadership discourse and practically to the empowerment of women in Islamic educational institutions. Keywords: Islamic Leadership; Spirituality; Social Transformation; Gender; Pesantren       Abstrak Penelitian ini mengeksplorasi model kepemimpinan Nyai Hj. Masriyah Amva, seorang ulama perempuan dan pengasuh Pondok Pesantren Kebon Jambu al-Islamy di Cirebon, Indonesia. Dalam struktur kepemimpinan pesantren yang secara historis bersifat patriarkal, peran beliau merepresentasikan pergeseran yang transformatif. Penelitian ini bertujuan untuk menganalisis spiritualitas Islam yang melandasi kepemimpinannya, mengidentifikasi transformasi sosial yang muncul sebagai dampak dari gaya kepemimpinannya, serta merumuskan model kepemimpinan transformasional berbasis integrasi antara spiritualitas dan perubahan sosial. Dengan pendekatan kualitatif dan metode studi kasus intrinsik, data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan studi dokumentasi. Temuan menunjukkan bahwa kepemimpinan Nyai Masriyah berakar pada spiritualitas etis dan profetik yang berfungsi secara vertikal (hubungan dengan Tuhan) dan horizontal (etika sosial). Kepemimpinan beliau telah memicu perubahan struktural dan kultural yang signifikan di lingkungan pesantren, seperti pelibatan perempuan dalam pengambilan keputusan, pengembangan kurikulum yang sensitif gender, dan keterlibatan luas dalam isu-isu sosial. Studi ini mengusulkan model konseptual Kepemimpinan Transformasional Islam yang berakar pada nilai spiritualitas, keadilan sosial, dan kesetaraan gender. Model ini menawarkan kerangka yang kontekstual dan dapat direplikasi, yang berkontribusi secara teoretis pada wacana kepemimpinan Islam dan secara praktis pada pemberdayaan perempuan di institusi pendidikan Islam. Kata kunci: Kepemimpinan Islam; Spiritualitas; Transformasi Sosial; Gender; Pesantren